APLIKASI SISTEM INFORMASI GAJI BERBASIS WEB DI STMIK PRADNYA PARAMITA DENGAN PENDEKATAN DATA WAREHOUSE - Mumpuni, Indah Dwi; Maknunah, Jauharul (Universitas Widyagama Malang, 2014)
The data warehouse is a concept and a combination of technologies that facilitate organizations to manage and maintain the historical data obtained from the operating system or application. This study discusses the application of data processing on a web-based payroll data warehouse approach in STMIK Pradnya Paramita Malang. The goal is to support the presentation of information in the decision making process both leaders, academic and financial sections. The method used is the method of analysis and design methods. Its design method that makes the application of information systems, data warehouse architecture design salary, Â database design and analysis of salary data tables. The method of analysis is done by using observation and interviews, literature studies, surveys directly by interviewing those involved to complete the required information . The end result of the application of data processing payroll information system using the web-based data warehouse is used to simplify and speed up data access and provide the leadership the full access to historical data without data processing operations. With the data warehouse can be generated structured data collection and integrates well as input for management in the decision making process.Keywords: Data Processing , Web , Data Warehouse , Salary, STMIK Pradnya Paramita Malang.